The Increasing of Brand Awarness Toward Social Media Instagram; A Customer Market Survey of Cafe in Indonesia - Renwarin, Joseph M.J. (AGUSPATI Research Institute, 2021)
The objective of this research is to know the effect of social media marketing through Instagram on brand awareness of Café Eat Happens. The research used quantitive approach with survey method. The sample in this research took 114 respondents who know Café Eat Happens through Instagram and visited Café Eat Happens at least once. The measurements used were questionnaires distributed through Google Form and manuals. Data were analyzed with SPSS 20.0. The result of T test shows that variable of information access and accessibility have no effect to brand awareness. While the variable of interactive capabilities and sharing of content have significant effects to brand awareness.